DETEKSI DINI DIABETES MELITUS GESTASIONAL MELALUI PEMERIKSAAN GLUKOSA DARAH DAN EDUKASI PENCEGAHAN KOMPLIKASI PADA IBU HAMIL DI DESA DELI TUA BARAT - Sitepu, Stefani Anastasia (INSTITUT KESEHATAN DELI HUSADA, 2025)
Pregnancy is a physiological condition experienced by a woman who will give birth to the next generation. During pregnancy, mothers should do Ante Natal Care (ANC) at least 4 times to maintain the health of the mother and fetus and prevent complications during pregnancy, childbirth, postpartum and the baby. Gestational Diabetes Mellitus (GDM) is a disorder that can occur in pregnant women. Gestational Diabetes Mellitus has short-term and long-term impacts on the mother and child. The impact is that the baby is born large, making it difficult for pregnant women and childbirth. Gestational Diabetes Mellitus (GDM) is a condition of glucose intolerance in pregnant women who have not previously been diagnosed with diabetes mellitus, so that in pregnant women there is an increase in glucose levels in the blood during pregnancy. This community service targets pregnant women with the aim of conducting early detection of GDM through fasting blood glucose examinations in pregnant women in Deli Tua Barat Village, Environment I - III. This activity was attended by 25 pregnant women as respondents, data collection was carried out by examining fasting blood glucose levels using test strips. The results of the examination showed that 10 pregnant women out of 25 respondents were detected with diabetes. It is expected that pregnant women can understand the importance of checking blood sugar levels during pregnancy. Method: conducting counseling and health checks, namely checking blood sugar levels.